The Relationship between Business Intelligence and Sustainable Human Resources - Al-kasasbeh, Omar; Badie’ Alhmoud (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The research explores the relationship between Business Intelligence (BI) and Sustainable Human Resource Management (Sustainable HRM), focusing on how BI tools enhance HR practices and contribute to organizational sustainability. As organizations strive for sustainable growth, the integration of BI with Sustainable HRM emerges as a critical strategy. The study addresses the gap in literature concerning the integration of BI in HRM and evaluates how BI-driven insights can improve HR decision-making, thereby enhancing organizational performance. The research questions focus on the dependencies between BI and HR, exploring the ways in which BI influences HR practices and sustainability outcomes. This study examines how BI aids in decision-making processes by providing comprehensive data analytics, thus fostering a dynamic and competitive business environment. Additionally, Sustainable HRM aligns HR practices with long-term organizational goals, emphasizing social responsibility, environmental care, and economic viability. Findings indicate that BI significantly enhances HR practices by providing data-driven insights that improve recruitment, training, and overall workforce management. However, challenges remain in aligning BI with HR strategies due to cultural and technological gaps. The study concludes that effective integration of BI into Sustainable HRM can lead to improved organizational sustainability, offering prescriptive advice for HR professionals to leverage BI tools for strategic decision-making. This research contributes to the fields of BI and HRM by demonstrating the critical role of BI in fostering sustainable HR practices, thereby promoting long-term organizational success